2019
DOI: 10.1136/jech-2019-212216
|View full text |Cite
|
Sign up to set email alerts
|

Life course socioeconomic position and incidence of mid–late life depression in China and England: a comparative analysis of CHARLS and ELSA

Abstract: BackgroundDespite the growing prevalence of depression in the Chinese elderly, there is conflicting evidence of life course socioeconomic position (SEP) and depression onset in China, and whether this association is akin to that observed in Western societies. We compared incident risk of mid–late life depression by childhood and adulthood SEP in China and England, a country where mental health inequality is firmly established.MethodsDepression-free participants from the China Health and Retirement Longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…This may be caused by the students with lower academic records having lower self-esteem and greater psychological pressure. Bad family economy means a higher rate of depressive symptoms, similar to results from a China and England longitudinal study [31]. However, in the current study, there was no correlation between depressive symptoms and gender, family structure, etc.…”
Section: Discussionsupporting
confidence: 86%
“…This may be caused by the students with lower academic records having lower self-esteem and greater psychological pressure. Bad family economy means a higher rate of depressive symptoms, similar to results from a China and England longitudinal study [31]. However, in the current study, there was no correlation between depressive symptoms and gender, family structure, etc.…”
Section: Discussionsupporting
confidence: 86%
“…One of the main findings of this study is that socioeconomic status is positively associated with sense of gain. This result is supported by previous empirical studies, which reveal that socioeconomic status have a significant predictive effect on higher sense of gain [11][12][13][14], lower negative affection and psychological symptoms(such as depressive symptoms, anxiety) [15][16][17][18][19], and higher well-being [20,21]. Moreover, Qiu [41] pointed out that the important issue concerning socioeconomic status is, "who gets what?…”
Section: Discussionsupporting
confidence: 77%
“…There are also studies that provide indirect evidence for the relationship between socioeconomic status and sense of gain. Empirical research has confirmed that people with lower socioeconomic status had more negative affection and psychological symptoms (such as depressive symptoms, anxiety) [15][16][17][18][19] and lowerwell-being [20,21]. For example, a longitudinal study found that lower socioeconomic status was associated with higher rates of depressive symptoms, and that among individuals with depressive symptoms, those with lower socioeconomic status were more likely to worsen and last longer [22].…”
mentioning
confidence: 99%
“…Moreover, subjective social class, a better predictor of health outcomes than objective social class [46], is strongly associated with depression [47]. Third, differences in social class may lead to inequalities in public mental health [48], which is a common determinant of depression in different social contexts [49]. Subjective social class is the social stratification perceived by individuals through social comparison, which has a significant psychological effect of social isolation.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%